Reduced Expression of METTL3 Promotes Metastasis of Triple-Negative Breast Cancer by m6A Methylation-Mediated COL3A1 Up-Regulation - Shi, Yu; Zheng, Chunlei; Jin, Yue; Bao, Bowen; Wang, Duo; Hou, Kezuo; Feng, Jing; Tang, Shiying; Qu, Xiujuan; Liu, Yunpeng; Che, Xiaofang; Teng, Yuee (Frontiers in Oncology, 2020)
The abnormal m6A modification caused by m6A modulators is a common feature of various tumors; however, little is known about which m6A modulator plays the most important role in triple-negative breast cancer (TNBC). In this study, when analyzing the influence of m6A modulators (METTL3, METTL14, WTAP, FTO, and ALKBH5) on the prognosis of breast cancer, especially in TNBC using several on-line databases, methyltransferase-like 3 (METTL3) was found to have low expression in breast cancer, and was closely associated with short-distance-metastasis-free survival in TNBC. Further investigation showed that knockdown of METTL3 could enhance the ability of migration, invasion, and adhesion by decreasing m6A level in TNBC cell lines. Collagen type III alpha 1 chain (COL3A1) was identified and verified as a target gene of METTL3. METTL3 could down-regulate the expression of COL3A1 by increasing its m6A methylation, ultimately inhibiting the metastasis of TNBC cells. Finally, with immunohistochemistry staining in breast cancer tissues, it was proved that METTL3 expression was negatively correlated with COL3A1 in TNBC, but not in non-TNBC. This study demonstrated the potential mechanism of m6A modification in metastasis and provided potential targets for treatment in TNBC.